PENGARUH COVID-19 TERHADAP KENAIKAN PENJUALAN TANAMAN HIAS KIOS RACHEL DI DESA REMBANG, KABUPATEN KEDIRI - Bukhorida, Febby Faradella; Febriani, Diyah Putri (Universitas Nusantara PGRI Kediri, 2021)
SARS COVID-19 virus spreading rapidly throughout the world, including Indonesia. Causing a change the pattern of people's lives. In order to prevent the spread of the virus, people should doing activities from home. Many activities to relieve boredom. One of is caring for ornamental plants, recently become a new hobby. Causing increased sales in the ornamental plant sector. The purpose of this research was to determine the increase in sales of Kios Rachel ornamental plants during the pandemic. This research uses a qualitative method by interviewing the seller of Kiosk Rachel, Rembang, Kediri. Using purposive sampling technique. Primary data from interviews and secondary data cites literature related research. Results showed sales of Kios Rachel during the pandemic influenced by several factors, the development of consumers from various circles and regions. The development of ornamental plants with varied prices. The results as well as the turnover of Rachel's Kiosduring the pandemic continued to increase.